Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s13018-019-1265-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approaches and outcomes for cervical myelopathy with increased signal intensity on T2-weighted MRI: a meta-analysis

Abstract: Objective Increased signal intensity (ISI) on T2-weighted magnetic resonance imaging (MRI) often indicates severe compression in patients with cervical myelopathy (CM). The optimal surgical approach for CM patients with ISI on T2-weighted MRI remains unclear. This meta-analysis aims to compare the clinical outcomes between anterior and posterior approaches for the treatment of these patients. Methods MEDLINE, EMBASE, Web of Science, and Chinese National Knowledge Infras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…The aim of MRI is to help diagnose and manage patients earlier, especially those with rp-CSM [ 11 ]. In our study, 88.2% of rp-CSM patients presented with MR T2-hyperintense lesions, which was a risk factor, as reported previously by Morishita et al [ 4 , 5 , 10 13 ]. On MRI, T2-hyperintense changes are considered to reflect the pathologies of spinal cord injury, such as edema, gliosis, demyelination, and myelomalacia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The aim of MRI is to help diagnose and manage patients earlier, especially those with rp-CSM [ 11 ]. In our study, 88.2% of rp-CSM patients presented with MR T2-hyperintense lesions, which was a risk factor, as reported previously by Morishita et al [ 4 , 5 , 10 13 ]. On MRI, T2-hyperintense changes are considered to reflect the pathologies of spinal cord injury, such as edema, gliosis, demyelination, and myelomalacia.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the rp-CSM patients showed good neurological recovery after surgery, indicating that this condition could be reversible. The optimal surgical timing and approach are still controversial and can vary depending on multiple factors, such as the location of the spinal cord compression, affected levels, and patient comorbidities [ 12 , 13 , 15 19 ]. In our study, rp-CSM patients had a shorter waiting period to surgery because of rapidly progressive neurological deterioration, and earlier decompression was considered.…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis suggested that anterior procedures result in better postoperative neural function than posterior procedures. 17 In addition, Huang et al. 18 revealed that anterior corpectomy had a higher reoperation rate, longer operation time, and greater blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis suggested that anterior procedures result in better postoperative neural function than posterior procedures. 17 In addition, Huang et al 18 revealed that anterior corpectomy had a higher reoperation rate, longer operation time, and greater blood loss. Liu et al 19 reported that anterior corpectomy and fusion was the preferred treatment for patients with fewer than three surgical segments, and a posterior procedure was recommended for patients with three or more levels of myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, the diagnosis of degenerative cervical myelopathy is often difficult early in the clinical presentation, predicting progression is complex, and optimal management strategies are unclear. [1][2][3][4][5] Magnetic resonance imaging (MRI) is an important diagnostic imaging modality for degenerative cervical myelopathy in which a hyperintense signal on T2-weighted imaging may represent spinal cord edema or contusion in the setting of acute symptoms, or myelomalacia in the setting of chronic spinal cord damage, 6 and is associated with worse clinical outcomes. 3,[7][8][9] In patients with moderate to severe degenerative cervical myelopathy, decompressive surgery limits neurological deterioration and improves outcomes.…”
mentioning
confidence: 99%